Diversidade taxonômica, funcional e filogenética de peixes recifais da Paraíba - Medeiros, Aline Paiva Morais de (2022)
In this thesis I evaluated how the reef fish diversity is distributed along natural reefs, including shallow and deep reefs, and centenary shipwrecks located along the continental shelf of Paraíba, Brazil. Specifically, the goals were to carry out a literature review on the use and misuse of ‘diversity’ metrics in studies of reef fish communities, and to estimate, in multiple spatial scales (alpha, beta and gamma), the taxonomic, functional and phylogenetic diversity of reef fish communities. I organized the thesis into three chapters. The first chapter corresponds to an extensive literature survey in which my colleagues and I synthesize the metrics most used on reef fish diversity studies since 1970. We highlight that the majority of studies have been applying ‘entropy’ metrics, which have serious mathematical limitations, rather than properly ‘diversity’ estimators. Most studies lack information on the spatial component of diversity (i.e. beta) and when this component is used, they are actually ‘entropy’ estimators, which are dependent on alpha diversity. Only few studies have been adequately estimating the functional and phylogenetic components of diversity of reef fish communities, despite of their relevance to management and conservation strategies. The second chapter was dedicated to compare shallow and deep natural reefs, which the main goal was to test the deep reef refuge hypothesis (DRRH). We surveyed 22 reefs, located along a depth gradient (2-62 m), and partitioned the gamma (regional) diversity into its alpha (local) and beta (the difference between two areas) independent components to estimate the taxonomic, functional and phylogenetic diversity. Although some data support the DRRH, most results indicate that the reef fish diversity of shallow reefs are not fully encapsulated in the deep reefs. Each reef contributes significantly to the regional diversity and should be managed and protected accordingly. In the third chapter, we compared the fish community between 4 artificial reefs (i.e. accidentally shipwrecked vessels dating from 1873 to 1926) and 8 natural reefs under the same methodological approach applied in second chapter. The goal was to evaluate whether artificial reefs increase or diminish the fish diversity, and the role they play on structuring the diversity on a spatial scale. Artificial reefs showed higher alpha and gamma diversity than their natural counterparts, most likely because they ‘steal’ species from adjacent natural reefs. Conversely, artificial reefs showed lower beta diversity rates than natural reefs, indicating that these reefs are biologically more heterogeneous than those. Altogether, these results indicate that artificial reefs, even after one century of colonization, are unlikely to fully protect the regional fish diversity. Management and conservation initiatives to protect and restore reef fish diversity should prioritize the existing natural reefs. The sinking of artificial structures should be discussed secondarily, and if decided in favor, must be implemented and monitored with caution to avoid further degradation of adjacent natural reefs.